2004
DOI: 10.1144/1470-9236/04-013
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate in groundwater: a water company perspective

Abstract: More than 100 groundwater sources operated by Anglian Water Services are vulnerable to diffuse and point pollution, and 33 of these sources have nitrate concentrations in excess of 50 mg l −1 as NO 3 . Most time series nitrate data ‘recess’ to a long-term rising baseline, upon which seasonal variations and/or data scatter are superimposed. Investigations at boreholes abstracting from the Chalk aquifer show that concentrations decrease with depth below the water t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…reported by the European Environment Agency (1999) and those of Beeson and Cook (2004) who found a linear increase of 1.3, 0.87 and 0.5 mg NO 3 L -1 a -1 for three sites in the Chalk of eastern England. However these authors applied a different model to data from the Lincolnshire Limestone which used two separate trendlines for wet and dry periods and gave a zero overall trend.…”
Section: Nitrate Status Of Uk Groundwatersmentioning
confidence: 70%
“…reported by the European Environment Agency (1999) and those of Beeson and Cook (2004) who found a linear increase of 1.3, 0.87 and 0.5 mg NO 3 L -1 a -1 for three sites in the Chalk of eastern England. However these authors applied a different model to data from the Lincolnshire Limestone which used two separate trendlines for wet and dry periods and gave a zero overall trend.…”
Section: Nitrate Status Of Uk Groundwatersmentioning
confidence: 70%
“…Beeson and Cook (2004) showed that nitrate in abstracted groundwater from the Lincolnshire Limestone decreased during periods of low water levels. This could be interpreted as a loss of rapid routes to points of abstraction for high nitrate modern recharge in the upper part of the aquifer due to the low water level.…”
Section: 3mentioning
confidence: 99%
“…Nitrate (NO 3 ) pollution has become a significant issue in many countries owing to its adverse effects on human health and the environment, such as the eutrophication of surface water (Vitousek et al, 1997;Mason, 2002) and groundwater nitrate contamination (Beeson and Cook, 2004;Rao, 2006;Rivett et al, 2007). The microorganisms inhabiting either natural environments or artificial reactors have developed one or more mechanisms to reduce nitrate to maintain the N-cycle balance.…”
Section: Introductionmentioning
confidence: 99%